1994
DOI: 10.1099/00221287-140-4-915
|View full text |Cite
|
Sign up to set email alerts
|

Transposon-mediated mobilization of chromosomally located catabolic operons of the CAM plasmid by TOL plasmid transposon Tn4652 and CAM plasmid transposon Tn3614

Abstract: The CAM (camphor degradation) plasmid is integrated into the chromosome of Pseudomonas putida Paw-line strains and is not selftransferable as a plasmid via conjugation. Our results show that the mobilization of chromosomally located CAM and the integration of cam-operons into the chromosome of the new Cam+ transconjugants is a red-independent process mediated by transposons Tn4652 (17 kbp) and Tn3614 (7.2 kbp). Transposon Tn3674 is apparently identical to the left-hand and the right-hand sequences of the TOL p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Bacterial transposons play an important role in the degradation of xenobiotic compounds, due to their catabolic activities. Maet and Heinaru (1994) reported that the transposons Tn4652 and Tn3614 play a key role in the evolution of Pseudomonas and spread of new catabolic plasmids in nature.…”
mentioning
confidence: 99%
“…Bacterial transposons play an important role in the degradation of xenobiotic compounds, due to their catabolic activities. Maet and Heinaru (1994) reported that the transposons Tn4652 and Tn3614 play a key role in the evolution of Pseudomonas and spread of new catabolic plasmids in nature.…”
mentioning
confidence: 99%